Regulation of Chromosome Replication in Bacillus subtilis: Effects of Amino Acid Starvation in Strain 168 - Copeland, James C. (1969)
Regulation of chromosome replication in Bacillus subtilis strain 168, in response to starvation for an essential amino acid, was found to differ from that reported for Escherichia coli. Not all replication points stop at the terminus during amino acid starvation. There is some evidence, however, to indicate that preferred stopping sites might exist. Initiation at the origin can occur in the absence of total protein synthesis as well as when the deoxyribonucleic acid (DNA)- mass ratio is unbalanced. DNA synthesis appears to be controlled independently of the initiation event by a second regulatory circuit, that may utilize the DNA-mass ratio. Once initiated, chromosome replication does not always go to completion in an uninterrupted sequence.